Genome-Wide Identification of Circular RNAs in Response to Low-Temperature Stress in Tomato Leaves - Yang, Xuedong; Liu, Yahui; Zhang, Hui; Wang, Jinyu; Zinta, Gaurav; Xie, Shangbo; Zhu, Weimin; Nie, Wen-Feng (Frontiers in Genetics, 2020)
Abiotic stress adversely inhibits the growth and development of plants, by changing the expression of multiple genes. Circular RNAs (circRNAs), as a class of non-coding RNAs, function in transcriptional and posttranscriptional regulation. Yet, the involvement of circRNAs in abiotic stress response is rarely reported. In this study, the participation and function of circRNAs in low-temperature (LT)-induced stress response were investigated in tomato leaves. We generated genome-wide profiles of circRNAs and mRNAs in tomato leaves grown at 25°C room temperature (RT) and 12°C LT. Our results show that 1,830 circRNAs were identified in tomato leaves in both RT and LT treatments, among which 1,759 were differentially induced by the LT treatment. We find that the identified circRNAs are mainly located at exons of genes, but less distributed at introns of genes or intergenic regions. Our results suggest that there are 383 differentially expressed circRNAs predicted to function as putative sponges of 266 miRNAs to target 4,476 mRNAs in total. Moreover, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis assays indicate that multiple pathways were enriched in both differentially expressed genes induced by LT and parental genes of differentially expressed circRNAs induced by LT, revealing the key functions of circRNAs and the corresponding targeted genes in response to LT stress. Our results suggest that circRNAs may be involved in regulating metabolism (i.e., carbohydrate, amino acid, lipid, and energy), signal transduction, and environmental adaptation-related pathways and that these circRNAs were predicted to regulate the expression of transcription factors, genes in signal transduction pathways, and genes related to the Ca2+ channel through targeting the corresponding proteins, such as WRKY, NAC, cytochrome P450, and calmodulin binding protein. Taken together, our study uncovers that multiple circRNAs are isolated and differently regulated in response to LT stress and provides the resource and potential networks of circRNA–miRNA–mRNA under LT stress for further investigations in tomato leaves.